(untitled) (Journal for Studies in Humanities and Social Sciences, 2017)
In Zimbabwe, autobiographies, particularly political ones, are sites of contestations, compositions, decompositions and recompositions of national narratives. In their obsession with the self, they always centre the narrating subjectivity whilst at the same time decentering and recentering others. This means that in this literary gamesmanship, certain political personalities are displaced, peripherised, and debunked in this historical re-imagination. Tekere in his autobiography, A Life time of Struggle (2007), seeks to impose his political credentials and legitimacy in the national script in the face of what he sees and stigmatises as opportunism by many politicians, and how these politicians were catapulted into positions of power by default. To dramatise this, his autobiography employs binary tropes that mark him out as iconic and a quintessence of virtue as opposed to the insipid, dour, corrupt and wishy-washy others. In this paper we argue that Tekere’s autobiographical act, coming as it does after he has been pushed outside the ruling circles, is meant to portray him as the personification of revolutionary incorruptibility which both the colonial and postcolonial regimes felt threatened by. This autobiography is, therefore, a conscious and deliberate act of inscribing the self into the Zimbabwean historico-literary landscape. It presents an alternative frame to the hegemonic master-discourses of the fetishised, Mugabe-centred patriotic history on and about Zimbabwe.